PENGARUH HASIL PROGRAM PARENTING DAN POLA ASUH ORANG TUA TERHADAP PENINGKATAN MOTIVASI BELAJAR ANAK USIA DINI - friska Friska Indria Nora Harahap (Al-Muaddib : Jurnal Ilmu-Ilmu Sosial & Keislaman, 2018)
This research is motivated by pebedaan motivation to learn every child, this is because difference of parenting pattern applied by parent to child. Patterns of parenting that is the pattern of foster democratic, authoritarian and permissive. Lack of parental knowledge about parenting is one of the factors that hinder children's learning motivation. But the knowledge is not only obtained by parents when the parenting program, some parents are able to obtain information about the care of other sources and able to provide good parenting. On the other hand, some other parents are not actively seeking information outside the activities that have been set. The purpose of this study is to provide information about: (1) the effect of parenting program on parenting parenting, (2) the influence of parenting pattern applied by parents (3) the influence of parenting program result and parenting pattern applied by parents to the improvement of early childhood learning motivation.The study of the theory used in this research consisted of the concept of parenting, the concept of parenting program, the concept of early childhood education, the concept of parenting in the family, and the concept of early childhood motivation.This research used survey method with cross-sectional study.Data approach collected using questionnaire technique. The population of this study were parenting participants in kindergarten ABA 3 Padangsidimpuandengan sample size 50 people.Based on the results of the study, the following conclusions are concluded: (1) parents who participate in parenting program in ABA 3 kindergarten Padangsidimpuansebanyak can apply the materials delivered at the time the activities are carried out into the care of children every day. (2) parenting parenting partially influences to the improvement of early childhood learning motivation, (3) parenting program result and parenting pattern which together influence to motivation of early child learning. Keywords: Parenting Program, Parents Parenting Patterns, Learning Motivation Early childhood.